Odpowiedzi

2009-12-19T16:44:02+01:00
Y=-3 - 3 x
-x + 3y = 11

pierwsze przepisujemy
-x + 3(-3 -3x)=11

pierwsze przepisujemy
- x - 9 - 9x =11

pierwsze przepisujemy
-9 - 10x= 11

pierwsze przepisujemy
-10 x= 11 +9

pierwsze przepisujemy
-10 x= 20/: - 10

pierwsze przepisujemy
x= -2

y= -3 - 3 * (-2)
x=-2

y=-3 * 6
x=-2

y= - 18
x= -2
1 5 1
2009-12-19T16:56:55+01:00
3x+y=-3
-x+3y=11


y=-3-3x
-x=11-3y

y=-3-3x
x=-11+(-9)-9x

y=-3-3x
x=-20-9x

y=-3-3(-20-9x)
x=-20-9x

y=-3+60+27
x=-20-9x

y=84
x=-20-9

y=84
x=-29
1 5 1